Pengaruh Opini Audit, Financial Distress, Dan Pertumbuhan Perusahaan Klien Terhadap Auditor Switching Di Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Sambo, Eva Marin; Aurelia S , Ade (Insan Cita Bongaya Research Journal, 2022)
This study aims to determine whether audit opinion, financial distress and the growth of client companies have an effect on manufacturing companies listed on the Indonesia Stock Exchange. Data collection uses secondary data obtained from annual financial statements of manufacturing companies listed on the Indonesia Stock Exchange with documentation techniques. The population is manufacturing companies listed on the Indonesia Stock Exchange with a total of 139 companies, while the sample taken is 54 companies. Methods of data analysis using logistic regression analysis. The results of this study show that the Audit Opinion, Financial Distress and Growth of the Client Company have no effect on Switching Auditors at Manufacturing Companies listed on the Indonesia Stock Exchange in 2017-2019.